Off-budget revenues and debt limit in municipalities in the Wielkopolska - Anna Białek-Jaworska; Robert Jaworski; Artur Wachowiak (Rozwój Regionalny i Polityka Regionalna)
The paper aims to assess whether the size of municipal off-budget activities carried out by municipally-owned companies (MOCs) depends on the municipality’s outstanding debt and unused debt capacity. The fiscal debt rule limits municipal debt capacity based on the individual debt ratio. In other words, the article attempts to establish whether and to what extent the size of off-budget financing through fees for local public services provided by MOCs depends on the municipality’s financial situation. We use panel data of 89 municipalities in Wielkopolska voivodeship (499 observations) retrieved from consolidated financial statements, reports on surplus/deficit of municipalities for 2010–2018, the Bank of Local Data and information on the MOC’s ownership structure and revenue volume obtained from the Orbis database. The models were estimated by the General Method of Moments (GMM) on a total sample of all municipal shareholders of MOCs in the Wielkopolska voivodeship. We show that municipalities shifted off-budget activities in response to fiscal debt limit restrictions valid since 2014 and election years. Furthermore, the structure and size of budgeted activity are linked to municipal activities’ relative opportunity costs. It is because increasing municipal fees generates lower political costs than raising taxes or local fees. Thus, we show that the fiscal debt constraint introduced in 2014 raises the scale of shifting expenditure off-budget using MOCs in the Wielkopolska voivodeship.